Effects of Lipid-Modifying and Other Drugs on Lipoprotein(a) Levels-Potent Clinical Implications - Amalia Despoina Koutsogianni; George Liamis; Evangelos Liberopoulos; Petros Spyridonas Adamidis; Matilda Florentin (MDPI AG, 2023)
The past few years have shown an ongoing interest in lipoprotein(a) (Lp(a)), a lipid molecule that has been proven to have atherogenic, thrombogenic, and inflammatory properties. Several lines of evidence, indeed, have demonstrated an increased risk of cardiovascular disease as well as calcific aortic valve stenosis in patients with elevated Lp(a) levels. Statins, the mainstay of lipid-lowering therapy, slightly increase Lp(a) levels, while most other lipid-modifying agents do not significantly alter Lp(a) concentrations, except for proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. The latter have been shown to reduce Lp(a) levels; however, the clinical significance of this effect has not been clearly elucidated. Of note, the pharmaceutical lowering of Lp(a) may be achieved with novel treatments specifically designed for this purpose (i.e., antisense oligonucleotides (ASOs) and small interfering RNAs (siRNAs)). Large clinical trials with cardiovascular outcomes with these agents are ongoing, and their results are eagerly awaited. Furthermore, several non-lipid-modifying drugs of various classes may influence Lp(a) concentrations. We have searched MEDLINE, EMBASE, and CENTRAL databases up to 28 January 2023 and summarized the effects of established and emerging lipid-modifying drugs and other medications on Lp(a) levels. We also discuss the potent clinical implications of these alterations.